The risk management committee’s structure and effectiveness on Malaysian public listed companies’ financial performances / Flicia Rimin - Rimin, Flicia (2021)
Risk management is a prevalent concept that underlines the value of providing good quality control and risk management functions to effectively monitor the corporate risk management framework. Researchers argued that an organization that develops a Risk Management Committee (RMC) is capable of focusing on risk issues, thereby efficiently monitoring risk and managing an internal control system. Previously, the MCCG 2007 mandated listed companies to include a risk management team in the internal audit committee to assess the efficacy of the organization's risk management, internal control, and governance process. However, due to recent corporate failures and ineffectiveness of audit committee to monitor firm performance, there is a growing need for a separate RMC. Researchers argued that it is not reasonable to expect audit committees to conduct a higher degree of risk analysis when their members have limited ability and time resources. In fact, risk is more than a financial context description; it includes operational, economic, sustainability, enforcement, technology and more. The purpose of the study is therefore to analyse the risk management committee‘s structure and effectiveness distinguishing across three (3) methods of analysis; 1) a separate RMC; 2) a combined RMC; and 3) an overall analysis on the firm financial performances of listed companies in Malaysia. The study period is 11 years (2008-2018) and the research is based on a Static Panel data technique involving regression based on FEM, Random Effect Model (REM) and Pooled Ordinary Least Square (OLS). The findings indicate that a company that set up an RMC consisting of a majority of independent non-executive directors, specifically a separate RMC, would significantly improve the firm's performance. The latter results support Agency Theory which suggests that independent non-executive directors enhanced the transparency of corporate boards as they improved the firm‘s compliance with the disclosure requirements. vandalism index under < 20%). In the future, urban tree monitoring programmes performing the tree assessment tasks are expected to consider this tree vandalism model. Hence, the tree vandalism status can be used to guide decision-makers and tree managers in improvement and rectification of decisions.